Volume 2A: Structures, Safety, and Reliability 2020
DOI: 10.1115/omae2020-18628
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mean Tension on Mooring Line Fatigue Life

Abstract: Studies published in recent years have documented a significant mean load effect on fatigue capacity for offshore mooring chain, and show that a reduction of the mean load gives an increase in fatigue life. However, current S-N design curves are based on fatigue tests performed at a mean load of 20% of minimum breaking load (MBL), which is well above the typical mean loads for most mooring systems. This paper investigates the mean loads experienced during fatigue damage accumulation for the moor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…When only the mean load effect is included, the fatigue damage at the end of the service life is 36% of the reference value. This is slightly higher than reported in [13], which is consistent with the previous comparison to the SWT curve (Fig. 7).…”
Section: Impact On Calculated Mooring Line Fa-tigue Lifesupporting
confidence: 93%
See 2 more Smart Citations
“…When only the mean load effect is included, the fatigue damage at the end of the service life is 36% of the reference value. This is slightly higher than reported in [13], which is consistent with the previous comparison to the SWT curve (Fig. 7).…”
Section: Impact On Calculated Mooring Line Fa-tigue Lifesupporting
confidence: 93%
“…Based on this transformation, they calculated S-N curve parameters at different mean load levels and established a S-N design curve for studless chain with parameterized dependence on mean load. Lone et al [13] used this capacity model to calculate mooring line fatigue damage for a typical production semi-submersible in the Norwegian Sea, and showed that the calculated fatigue damage was reduced by a factor of 2.5-3.0 depending on the orientation of the line. These factors should however be regarded as upper limits for fatigue damage reduction for the unit considered, as the negative effect of corrosion was not accounted for.…”
Section: Effect Of Mean Loadmentioning
confidence: 99%
See 1 more Smart Citation